2019
DOI: 10.3390/molecules24213994
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Study of Immunostimulation by Leuconostoc lactis-Produced Gluco-Oligosaccharides

Abstract: Glycosyltransferase-producing Leuconostoc lactis CCK940 produces CCK- oligosaccharides, gluco-oligosaccharide molecules, using sucrose and maltose as donor and acceptor molecules, respectively. In this study, the immunostimulatory activities of CCK-oligosaccharides on RAW264.7 macrophages and BALB/c mice were evaluated. CCK-oligosaccharides induced the expression of phosphorylated-p38, extracellular-signal-regulated kinase (ERK), and c-Jun N-terminal kinase (JNK) and upregulation of phagocytic activity in RAW2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
(54 reference statements)
2
8
0
Order By: Relevance
“…Chung also reported that Eubacterium eligens , a species belonging to Firmicutes, utilizes apple pectin as a prebiotic source and promotes the production of the anti-inflammatory cytokine IL-10 in host cells [ 54 ]. Although some studies have explored the immunomodulatory activity of gluco-oligosaccharides, there has been no study on the anti-inflammatory activity of gluco-oligosaccharides [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chung also reported that Eubacterium eligens , a species belonging to Firmicutes, utilizes apple pectin as a prebiotic source and promotes the production of the anti-inflammatory cytokine IL-10 in host cells [ 54 ]. Although some studies have explored the immunomodulatory activity of gluco-oligosaccharides, there has been no study on the anti-inflammatory activity of gluco-oligosaccharides [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Typically, oligosaccharide-producing LAB include the genera Leuconostoc , Weissella , Streptococcus , Lactobacillus , and Oenococcuss ; these LABs synthesize oligosaccharides by the action of glucansucrase (EC 2.4.1.5), a type of glycosyltransferase, using sucrose as substrate. In addition to glucansucrase, mutansucrase (EC 2.4.1.5), alternansucrase (EC 2.4.1.140), and levansucrase (EC 2.4.1.10) synthesize oligosaccharides with different structures [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunostimulatory potential of probiotics may be useful for the prevention and treatment of complex disorders ranging from diarrhea to allergy. Several LABs, including Lactococcus , Enterococcus , Lactobacillus and Leuconostoc , have been reported to have beneficial health effects by stimulating the immune system [ 19 , 20 , 21 , 22 , 23 ]. The immunostimulatory mechanism of LAB comprises regulation of the T cell effector subset, the improvement of humoral immunity and activation of macrophages and lymphocytes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although the immuno-promoting efficacy of lactic acid bacteria (LAB) has been actively studied, the efficacy of some specific strains have not been characterized; thus, further studies on various strains and the mechanisms of action are required [ 18 ]. Among the 13 genera of LAB, Lactococcus , Lactobacillus , Leuconostoc and Enterococcus are known to play key roles in improving immunity, maintaining intestinal microbial balance and preventing gastrointestinal infections [ 19 , 20 , 21 , 22 , 23 ]. Recent studies have shown that selenium exopolysaccharide produced by Lactococcus lactis subsp.…”
Section: Introductionmentioning
confidence: 99%